THE ANALYSIS OF DESCRIPTIVE STATISTICS ON THE USE OF SYARIAH FINTECH IN INDONESIA - Sahlan Yahya; Bayu Arie Fianto (Universitas Airlangga, 2020)
This research presents a preliminary study on the use of Islamic fintech in terms of several aspects, namely, socio-economic aspects, geographical aspects, social influence, religiosity. Socio-economic aspects consist of gender, age, education level, income level, and type of work. Geographical aspects consist of the distance of residence from the nearest financial institution and location of residence. Data is collected by giving questionnaires to users of Islamic fintech and non-users of Islamic fintech. The results of this study are in the form of an explanation or excavation of information related to which aspects show the difference between users and non-users of Islamic fintech. This research was conducted because of the lack of research about the use of Islamic fintech in terms of various aspects above. This study contributes to the behavior of Indonesian people in utilizing Islamic fintech as a provider of Islamic financial services in the Industrial Revolution 4.0 era.Keywords: Islamic fintech, socioeconomic aspects, geographical aspects, social influence, religiosityREFFERENCESAfifuddin dan Beni Ahmad Saebani. 2009. Metodologi penelitian kualitatif. Bandung: Pustaka Setia.Arif, M Nur Rianto Al. 2015. Pengantar Ekonomi syariah teori dan praktik. Bandung: Pustaka Setia.Astuti, Rika Pristian Fitri. 2016. Pengaruh Status Sosial Ekonomi Orang Tua, Literasi Ekonomi dan Life Style Terhadap Perilaku Konsumsi Mahasiswa Jurusan pendidikan Ekonomi IKIP PGRI Bojonegoro. Bojonegoro: Fakultas Pendidikan Ilmu Pengetahuan Sosial. Jurnal Edutama. Vol 3, no. 2 Juli 2016Bachri, Bachtiar S. 2010. Meyakinkan Validitas Data Melalui Triangulasi Pada Penelitian Kualitatif. Universitas Negeri Surabaya. Vol. 10, No. 1, hal 46-61.Baidhowi, Bagus dan Irham Zaki. 2014. Implementasi konsumsi Islam Pada Pengajar Pondok Pesantren (Studi Kasus Pengajar Pondok Pesantren Aqobah Kecamatan Diwek Kabupaten Jombang). Universitas Airlangga. Vol. 1, No. 9.Chan, Arianis. 2010. Pengaruh Ekuitas Merek Terhadap Proses Keputusan Pembelian Konsumen:Sstudi Kasus Bank Muamalat Indonesia Cabang Bandung. Universitas Padjajaran. Jabv6n1.texFauzia, Ika Yunia dan Abdul Kadir Riyadi. 2014. Prinsip Dasar Ekonomi Islam perspektif Maqashid Syariyyah. Jakarta: KencanaIda, N. 2009. Pengaruh Ekonomi Mikro. Universitas Muhammadiah Malang Press. MalangKhan, M Fahim. 2014. Esai-Esai Ekonomi Islam. Jakarta: RajaGrafindo Persada Moleong, Lexy J. 2005. Metode Penelitian Kualitatif. Bandung: Remaja Rosdakarya.Panjaitan, Poopy. 2017. Pengaruh Social Media terhadap Produktifitas Kerja Generasi Millenial. Malang: Jurnal Administrasi BisnisPujiyono, Arief. 2006. Teori Konsumsi Islam. Jurnal Dinamika Pembangunan. III (2) : 196-207.Rosyidi, Suherman. 2006. Pengantar Teori Ekonomi. Jakarta: Raja Grafindo PersadaShihab, M. Quraish. 2004. Tafsir al-Mishbah: Pesan, Kesan dan Keserasian al-Qur’an. Jakarta: Lentera Hati. volume 1, cetakan. Ke 2.Siddiqi, Muhammad Nejatullah. 2004. Kegiatan Ekonomi dalam Islam. Jakarta: PT. Bumi AksaraSitepu, Novi Indriyani. 2016. Perilaku Konsumsi Islam Di Indonesia. Universitas Syiah Kuala Banda Aceh. Vol. 2, No. 1Sugiyono. 2014. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Sumar’in. 2013. EkonomiIslam: Sebuah Pendekatan Ekonomi Mikro Perspektif Islam. Yogyakarta: Graha IlmuSuwiknyo, Dwi. 2010. Kompilasi Tafsir Ayat-Ayat Ekonomi Islam. Yogyakarta: Pustaka Pelajar.Yin, Robert K. 2003. Studi Kasus (desain dan metode). Jakarta: PT Raja Grafindo Persada.Yin, Robert K. 2015. Studi Kasus: Desain dan Metode. Jakarta: PT Raja Grafindo